Powdered antibacterial agent
A zinc oxide-based powder antibacterial agent with a dispersant stabilizes nanoparticle size for durable antibacterial and antiviral performance, addressing durability and color change issues in textile products.
Patent Information
- Application Number
- JP2023110983
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-20
AI Technical Summary
Conventional antibacterial treatments for textile products suffer from durability issues due to decreased effectiveness with wear and washing, and can cause color changes such as yellowing, especially when using metal or inorganic compounds.
A powder antibacterial agent composed of 80 to 95% zinc oxide and 5 to 15% dispersant, which is processed into a slurry with an average particle size of 80-120 nm, maintaining stability and dispersibility, allowing for effective antibacterial and antiviral performance without color changes.
The powder antibacterial agent provides long-lasting antibacterial and antiviral protection, maintaining effectiveness through 80-120 washes and preventing color changes, suitable for both water-based and solvent-based processing environments.
Smart Images

Figure 2025008646000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a powdered antibacterial agent for use in materials for textile products and the like. [Background technology]
[0002] In recent years, as the focus on hygiene has increased for everyday textile products such as clothing textile products, futon covers, curtains, towels, and wall coverings, there has been active development of antibacterial and antifungal treatments for each textile product.
[0003] Among them, polyurethane elastic fibers are particularly widely used in clothing, and recently it has become common to impart antibacterial properties to such polyurethane products to prevent odors and infectious diseases.
[0004] For example, as shown in Patent Documents 1 to 3, a method that has been commonly used in the past for textile products is to attach natural organic substances such as antibacterial herbal medicines, chitosan, green tea catechins, and eucalyptus leaves and branches, and synthetic organic substances such as diamine chlorethane, quaternary ammonium salts, phosphobetaine, clotrimazole, tolnaftate, and undecylenic acid derivatives by post-processing.
[0005] Furthermore, as shown in Patent Documents 4 and 5, a method is known in which the above-mentioned antibacterial chemicals are mixed with a resin and then molded in order to improve the durability of the antibacterial effect. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2001-214368 A [Patent Document 2] Japanese Patent Application Publication No. 4-257301 [Patent Document 3] Japanese Patent Application Publication No. 5-44165 [Patent Document 4] Japanese Patent Application Publication No. 5-339811 [Patent Document 5] Japanese Patent Application Publication No. 4-228698 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the post-processing methods disclosed in Patent Documents 1 to 3, the effects gradually decrease with wearing and washing, and are not long-lasting. Furthermore, if one tries to prevent the effects from decreasing due to washing, there is a risk that the product will become hard.
[0008] In addition, in the processing methods disclosed in Patent Documents 4 and 5, metal compounds such as copper, silver, and zinc, inorganic antibacterial agents such as sulfur, and various organic antibacterial agents are used as antibacterial substances. However, by kneading these antibacterial agents into the resin, the physical properties of the fiber deteriorate and the fiber becomes prone to color changes such as yellowing over time.
[0009] The object of the present invention is to provide an antibacterial agent which is an improvement over antibacterial agents used in conventional textile product materials, etc., and which is excellent in storage properties and workability during production, maintains a relatively high level of antibacterial activity, and is capable of realizing the production of synthetic leather or textile apparel products, etc., without causing color changes such as yellowing. [Means for solving the problem]
[0010] The present invention relates to a powdered antibacterial agent which is a composition containing 80 to 95% by weight of zinc oxide and 5 to 15% by weight of a dispersant.
[0011] The powder antibacterial agent according to the present invention includes the following embodiments. (1) The composition is 27-33% by weight of zinc oxide, 6-15% by weight of dispersant, and 55-65% by weight of water, and is formed by spray-drying a slurry-type nanoparticle antibacterial processing agent with an average particle diameter of 80-120 nm in a slurry state. (2) The content in the target fabric is 0.2 to 0.5% by weight. Effect of the Invention
[0012] The powdered antibacterial agent of one or more embodiments of the present invention is a composition consisting of 80 to 95% by weight of zinc oxide and 5 to 15% by weight of a dispersant, and is excellent in storage properties and workability during production, maintains a relatively high level of antibacterial activity, and enables the production of synthetic leather or fiber apparel products and the like that do not undergo color changes such as yellowing. [Brief description of the drawings]
[0013] The drawings show specific embodiments of the powder antimicrobial agent according to the present disclosure, including essential configurations of the invention as well as alternative and preferred embodiments. [Figure 1] FIG. 2 is a schematic diagram showing a process for forming the powder antibacterial agent according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The powder antibacterial agent according to the present invention will be described in detail below with reference to the accompanying drawings.
[0015] As shown in FIG. 1, the powder antibacterial agent 1 of the present invention is a nanoparticle zinc oxide that is made by evaporating water from a slurry-type nanoparticle antibacterial agent (slurry-type nanoparticle zinc oxide agent) 2 through a special spray-drying process, and carrying a dispersant.
[0016] (General nanoparticle inorganic raw material) It has long been known that the antibacterial properties of inorganic raw materials such as silver, copper, platinum, titanium oxide, and zinc oxide can be improved by processing them into nanoparticles, thereby increasing their specific surface area.
[0017] For example, in the case of zinc oxide, the primary particles are nano-sized, so the average particle size is about 20 nm. However, if the average particle size is about 10 to 30 nm, aggregation begins immediately after production is completed, and the average particle size eventually increases to the 500 nm to 1 μm level.
[0018] If the average particle size exceeds 500 nm, the specific surface area decreases, leading to a decrease in antibacterial function. Also, if the fibers are simply nano-sized, the processing methods for resins are limited. When the object to be processed is a textile product, it is said that processing in a process that uses water, such as fabric processing, thread processing, and product processing, is the most efficient. However, if nano-particle type inorganic antibacterial raw materials are placed in water, they will separate and precipitate due to the difference in specific gravity, making processing impossible.
[0019] When the object to be processed is resin, a powder form is preferable since it is put into a solvent. However, this requires adjustments such as increasing the amount of solvent, and secondary factors can cause color changes, making the processing method more difficult. For these reasons, it can be said that simply putting nanoparticle-type inorganic antibacterial raw materials into water or a solvent does not make them an efficient antibacterial processing agent.
[0020] (Nanoparticle antibacterial agent) It is common to use inorganic raw materials such as silver, copper, platinum, titanium oxide, and zinc oxide, and to produce antibacterial processing agents by eluting ions with water or organic solvents. It is also possible to stabilize the nanoparticle size of the nanoparticle inorganic antibacterial raw materials by using a dispersant.
[0021] (Slurry-type nanoparticle antibacterial processing (trade name "Nanofine") The slurry-type nanoparticle antibacterial agent 2 before spray-drying of the powder antibacterial agent 1 according to the present invention is a composition consisting of 27-33% by weight of zinc oxide, 6-15% by weight of dispersant, and 55-65% by weight of water, and maintains an average particle diameter of 80-120 nm in the slurry state. As the same type of slurry-type nanoparticle antibacterial agent normally available on the market has an average particle diameter of about 300-500 nm, the slurry-type nanoparticle antibacterial agent 2 has overwhelmingly superior antibacterial performance.
[0022] Furthermore, in the case of textile products, washing durability is also required. The washing durability of a general antibacterial processing agent is about 15 to 25 washings. When the content of the antibacterial processing agent is increased to a concentration of 1.2 to 2.0% by weight, the washability tends to improve.
[0023] The slurry-type nanoparticle antibacterial agent 2 exhibits good antibacterial activity even after 80 to 120 washes at 0.3 to 0.7% by weight. In addition, stable processing can be achieved by processing according to a proprietary processing schedule, and processing can be carried out without the use of special equipment not only in Japan but also in overseas dye factories in China, Vietnam, Bangladesh, etc.
[0024] (Powdered antibacterial agent) The powder antibacterial agent 1 of the present invention is a nanoparticle sustained antibacterial agent that the applicant developed for antibacterial treatment in environments where water cannot be used, in addition to the slurry-type nanoparticle antibacterial agent 2 that is intended for antibacterial treatment in environments where water is used.
[0025] As mentioned above, the powder antibacterial agent 1 is a nanoparticle zinc oxide carrying a dispersant, produced by spray-drying the slurry-type nanoparticle antibacterial agent 2 using a special method and evaporating the water.
[0026] The powder antibacterial agent 1 has a composition of 80 to 95% by weight of zinc oxide and 5 to 15% by weight of an additive (dispersant).
[0027] The powdered antibacterial agent 1 enables processing at processing sites where water-based functional materials cannot be used. Normally, water-based functional materials that cause hydrolysis cannot be used in the production of polyurethane resins, but the powdered antibacterial agent 1 can be added to the solvent (methyl ethyl ketone, etc.) used in the production of urethane resins, etc. It is preferable to add the powdered antibacterial agent 1 in approximately the same weight ratio as the solvent.
[0028] Furthermore, since the powdered antibacterial agent 1 has excellent dispersibility, it disperses immediately when added to a solvent, facilitating preparation for processing.
[0029] Regarding the amount of powder antibacterial agent 1 used, for example, when the target processed product is synthetic leather (width 120 cm × length 100 m) with a thickness of 100 μm and polyurethane resin weight 30 kg, the amount of powder antibacterial agent 1 used is 0.25% by weight, so antibacterial processing can be performed with a total of 75 g of powder antibacterial agent 1. In order to exert its antibacterial and antiviral properties, the powder antibacterial agent 1 may be contained in a small amount relative to the target fabric made of synthetic leather or fiber, and specifically, a content of 0.2 to 0.5% by weight can exert the required effect.
[0030] <Method for measuring hydrolysis resistance of synthetic leather using powder antibacterial agent> Table 1 shows the results of measuring the peel strength and tear strength after a hydrolysis resistance test (jungle test conditions: temperature 70°C, relative humidity 95%, held for 4 weeks) on synthetic leather treated with a powder antibacterial agent, and observing the change in appearance. The appearance observation was evaluated according to the following criteria. ○: There is no change in the appearance of the synthetic leather after the test. △: Slight color change occurred in the synthetic leather after the test. ×: A significant color change occurred in the synthetic leather after the test.
[0031] [Table 1]
[0032] As shown in Table 1, the peel strength and tear strength after 1 to 4 weeks did not decrease significantly compared to before the test, and it can be said that there is no adverse effect such as deterioration on the physical properties of the urethane resin to be processed.
[0033] In addition, no color change was observed over time in the appearance observation evaluation. When the object to be processed is a light color, conventional antibacterial processing agents may cause color changes such as yellowing in the synthetic leather, but when the powder antibacterial agent 1 according to the present invention is used, color changes such as yellowing do not occur.
[0034] <Virus inactivation evaluation test> Table 1 below shows the test results of virus inactivation evaluation performed under the following conditions on treated fabrics using a powder antibacterial agent. Test method: The test was conducted according to the following procedure in accordance with ISO21702. 1) 0.1 ml of a 10-fold diluted influenza virus liquid for testing was dropped onto a sample measuring 5 cm x 5 cm, and a polypropylene (PP) resin film measuring 4 cm x 4 cm was then attached to the sample. 2) After leaving the plate at 25°C for 24 hours, the sample surface was washed with 5 ml of SCDLP medium by pipetting 10 times to recover any remaining viruses. 3) Furthermore, the recovered virus liquid was serially diluted 10 times with Eagle MEM medium. 4)10 6 The test solutions diluted up to 100% were subjected to plaque tests according to standard methods. Duration of action: 24 hours Test virus: Influenza virus (ATCC VK-1679 Influenza A virus (H3N2) Test cells: MDCK (derived from dog kidney) cells
[0035] As an example, a lining synthetic leather fabric was used, with a surface layer made of 100% polyurethane (PU) resin and a base fabric made of 100% polyethylene (PE) resin, and 0.25% by weight of a powdered antibacterial agent was added to the solvent during production.
[0036] In Comparative Example 1, a polypropylene resin film (blank) was used.
[0037] [Table 2]
[0038] As shown in Table 2, it was found that even the processed fabric containing a trace amount of powder antibacterial agent 1 (0.25% by weight) in the solvent had sufficient antiviral performance.
[0039] <Antibacterial test> The following Tables 3 and 4 show the results of antibacterial tests carried out under the following conditions on processed fabrics using the powder antibacterial agent 1 according to the above embodiment. Test method: The test was conducted in accordance with the JIS L1902 (2015) test method. Quantitative test: Bacterial liquid absorption method Method for measuring viable bacteria count: Pour plate culture method Test bacteria suspension: non-ionic surfactant (added at 0.05%) Sterilization method for test specimens: Autoclave Washing method: Washing method for textile products marked by the Japan Textile Evaluation Technology Council (standard washing method, hang dry) Test bacteria: 1) Staphylococcus aureus (Table 3) Inoculum solution concentration: 1.2×10 5 (CFU / ml) 2) Methicillin-resistant Staphylococcus aureus (Table 4) Inoculum solution concentration: 2.2×10 5 (CFU / ml)
[0040] [Table 3]
[0041] [Table 4]
[0042] A cotton cloth (standard cloth) was used as Comparative Example 2 for comparison with the Example. As shown in Tables 3 and 4, it was found that even the processed fabric containing a trace amount of powder antibacterial agent 1 of 0.25% by weight in the solvent had sufficient antibacterial performance before and after washing.
[0043] Since the powder antibacterial agent 1 of the present invention is kneaded into the resin material, it has a lower rate of falling off compared to products with antibacterial treatment applied to the surface, and can maintain its antibacterial performance semi-permanently as a product.
[0044] Furthermore, since the powdered antibacterial agent 1 is in the form of a powder, there is no need to worry about volatilization, evaporation, or solidification due to separation and precipitation, as occurs with liquid or viscous antibacterial agents, and it can be stored for a long period of time.
[0045] Furthermore, the powder antibacterial agent 1 exhibits sufficient antiviral and antibacterial performance even in small amounts; specifically, a content of about 30% of the slurry-type nanoparticle antibacterial processing agent 2 exhibits the same level of antiviral and antibacterial performance, which allows for reduction in transportation costs when shipping overseas, etc.
[0046] As described above, the powder antibacterial agent 1 can be used as a substitute for the conventional slurry-type nanoparticle antibacterial agent 2, and since textile products are processed in a process that uses water, adding a specified amount to the water to be used quickly disperses and completes the processing liquid. Also, in the case of the slurry-type nanoparticle antibacterial agent 2, there is a possibility that it may separate and settle during storage, so it is necessary to stir it in a stirrer, which is time-consuming, but in the case of the powder antibacterial agent 1, this work is not necessary, improving work efficiency.
[0047] As described above, the powder antibacterial agent 1 according to the present invention is used as a material for synthetic leather and textile products. For example, synthetic leather is made of a base fabric made of fibers and a resin skin layer formed on the surface of the base fabric. The base fabric is a woven fabric, knitted fabric, nonwoven fabric, etc., and examples of the fiber material constituting the base fabric include natural fibers such as cotton, hemp, and wool, synthetic fibers such as polyamide, polyester, and polyacrylonitrile, semi-synthetic fibers such as acetate, and regenerated fibers such as rayon. The fabric base material may be subjected to treatments such as scouring and dyeing under general conditions.
[0048] The main component constituting the resin skin layer is a synthetic resin, such as polyurethane resin, polyethylene resin, polypropylene resin, polyethylene resin, acrylic resin, urethane resin, epoxy resin, etc. The resin skin layer may contain additives such as pigments, dyes, silicone, etc. as other components.
[0049] The material for the textile product is not particularly limited, and various materials can be used, such as natural fibers such as cotton, linen, wool, and silk; regenerated cellulose fibers such as rayon, cupra, and Tencel (trademark); semi-synthetic fibers such as acetate and Promix; synthetic fibers such as polyamide fibers, polyester fibers, acrylic fibers, polyolefin fibers, polyvinyl chloride fibers, polyimide fibers, and polyurethane fibers; and composite fibers of these fibers.
[0050] In addition, products that use synthetic leather or fiber materials using the powder antibacterial agent 1 include, in addition to general clothing such as shirts, jackets, and underwear, towels, handkerchiefs, bedding, stockings, gloves, caps, dishcloths, wipers, cooking sheets, drip sheets, wet tissues, bedding (bed sheets, pillowcases, etc.), tote bags, slippers, tissue paper, nursing care products, dust collection filters, mops, foot mats, and clothing for hospitals and nursing facilities. [Explanation of symbols]
[0051] 1. Powdered antibacterial agent 2. Slurry-type nanoparticle antibacterial agent
Claims
1. A powdered antibacterial agent comprising a composition consisting of 80 to 95% by weight of zinc oxide and 5 to 15% by weight of a dispersant.
2. The powder antibacterial agent according to claim 1, which is formed by spray-drying a slurry-type nanoparticle antibacterial agent having an average particle size of 80 to 120 nm in a slurry state, the composition of which is 27 to 33% by weight of zinc oxide, 6 to 15% by weight of dispersant, and 55 to 65% by weight of water.
3. The powdered antibacterial agent according to claim 1 or 2, wherein the content of the powdered antibacterial agent in the target fabric is 0.2 to 0.5% by weight.
Citation Information
Patent Citations
Coated sheet for color printing
JP1992228698A
Antifungal and deodorizing leg product and its production
JP1992257301A
Antibacterial, mildew-proofing and deodorizing filament and nonwoven fabric
JP1993044165A
Production of antigerminal cellulose fiber
JP1993339811A
Antimicrobial fiber-finishing agent composition
JP2001214368A